Analisis Profil Antropometri, Status Gizi, Dan Kebugaran Jasmani Atlet Gulat Di Kabupaten Malang Dan Kota Malang - Azizah, Pipit Nur; Nurrochmah, Siti (Jurnal Porkes, 2024)
The purpose of this study was to determine and review information about anthropometry, nutritional status, and physical fitness. The research used an observation method approach and the data was analyzed using descriptive statistics in the form of central tendency. The research subjects were wrestling athletes in Pengcab. Malang Regency and City, each of which amounted to 20 athletes. So that the subjects studied amounted to 40 athletes. The results of anthropometric data analysis and nutritional status of Pengcab. Malang district, the men's group (45.45%) and the women's group (88.88%) are dominant in normal criteria, while in Pengcab. Malang city, the men's group (66.66%) and the women's group (75%) are dominant in normal criteria. The results of data analysis of physical fitness in pengcab. Malang regency, the men's group (45.45%) is dominant in good and moderate criteria, and the women's group (66.66%) is dominant in moderate criteria, while in pengcab. poor city, the men's group (66.66%) is dominant in moderate criteria and the women's group (87.5%) is dominant in moderate criteria. It can be concluded that most male and female athletes have nutritional status, measures of height, weight, upper arm circumference, and leg length which are categorized as normal / not at risk. The results of physical fitness data for male and female athletes have a fitness level of moderate criteria.